Efficient extraction of biodiesel feedstock and dehydration of kitchen waste: A method based on co-dissolution of liquefied dimethyl ether and water. (15th June 2022) - Sun, Jipeng; Zhu, Wei; Mu, Biao; Zhong, Jun; Lin, Naixi; Chen, Sipeng; Li, Zhuo
Graphical abstract: Highlights: A new method for addressing the problems of KW. L-DME has excellent ability for lipids extraction and dehydration of KW. The extracts are mainly composed of C18:2, C18:1, C16:0, and C18:0. The co-dissolution system of L-DME and water is the key to extract lipids. Abstract: In the context of low-carbon development, as a waste rich in lipids, kitchen waste (KW) has received increasing attention for resource utilization and low-carbon utilization. In this study, we explored a method for efficient extraction of lipids and dehydration using liquefied dimethyl ether (L-DME) to address the problem of high lipids and the difficulty of dewatering of KW. A closed DME reaction vessel was used to conduct experiments on the effects of lipids extraction and dehydration of KW under different reaction times, mass ratios, temperatures and moisture contents. It was found that DME could extract more than 90% of the lipids and the dehydration rate could reach approximately 80%. The main components of the lipids in the liquid phase extract were fatty acids (C18:2, C18:1, C16:0, and C18:0) whose good thermal properties made them suitable for use as a feedstock for biodiesel production. Moreover, the greatly increased heating value of the solid residue facilitated low-carbon utilization. This study also demonstrated a promotion effect of the co-dissolution system of L-DME and water on the extraction of lipids and explored the related mechanism.